The Tsunami of Digitalization of Health Care in the Pre and Post-COVID Era and Its Impact on the Indian Healthcare Industry – Situation Analysis - Rao, Jyoti (Digital Repository of Theses, 2024)
Purpose The healthcare system is trying to keep pace with the evolving times and the pressures have encouraged the acceptance and speed of adoption of digitalization. There is scarcity of empirical evidence and evaluation regarding the effectiveness and sustainability of digital health initiatives. Especially from the Indian context, we need research which identifies the competency of health care workers and opportunities, challenges, barriers and pitfalls, system preparedness which support/hinder digital technology adoption, particularly in the pre-and post-Covid era. Method Three cross-sectional surveys were conducted targeting health care workers and health care administrators from large, medium and small sized hospitals located in Tier 1, 2 and 3 cities of India. The cross-sectional survey explored the demographic features, competencies, challenges and preparedness as reported by the participants by using a mixed-method approach, with both close ended and open-ended questions. Results 151 healthcare workers, 64 health care managers and 25 health care administrators participated in the three surveys. The competencies of health care professionals in knowledge, skills and ease of use have increased significantly post-Covid. All have reported high motivation levels. While the focus was on adoption of new technology and finances in the pre-Covid era, the primary focus has been on human resource development and patient safety and patient compliance in the post-covid era. Patient data safety remains the most widely reported ethical concern. Participants specified the impact of digitalisation on patient interaction, team collaboration, patient safety and health equity to be both positive and negative, depending on the context. Participants expressed that they needed ‘In-depth and frequent training’, ‘Budget and ‘manpower allocation’, ‘Active monitoring and awareness’ for improving their digital health care delivery competence. Conclusion This is the first study to provide empirical evidence on self-reported competencies, opportunities, challenges and organizational preparedness from the health care workers and health care administrators’ perspective. To increase the digital technology adoption, there is need for enhanced human resource training and address ethical issues of patient data safety.